KEBIJAKAN PENGEMBANGAN PARIWISATA ALAM DI KECAMATAN XIII KOTO KAMPAR TAHUN 2017-2018 - Muhammad Fadillah; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The policy of the Kampar Regency Tourism and Culture Office in tourism development in Kampar Regency is very important for its progress in supporting the success of national tourism development. The Department of Tourism and Culture of Kampar Regency is obliged to consistently manage the potentials that can be developed, one of which is the development and development of natural tourism in XIII Koto Kampar District, which is expected to improve the welfare of the community. This study aims to determine how the implementation of the policies of the Kampar Regency Tourism and Culture Office in the development of natural tourism in XIII Koto Kampar District and to determine the inhibiting factors in the development of natural tourism.This research use desciptive qualitative approach. Then the data collection techniques used were interviews, observation, and documentation. While the data analysis technique was carried out by collecting information through interviews, data reduction and data presentation.The results of this study indicate that the implementation of policies carried out by the Department of Tourism and Culture of Kampar Regency in the development of natural tourism in the XIII Koto Kampar District has not been carried out optimally, the communication carried out in the development of natural tourism in the XIII Koto Kampar District is carried out by means of socialization and promotion to the community. . There are still obstacles found in the development of natural tourism in the XIII Koto Kampar District, such as inadequate human resources both in terms of quality and quantity, limited budget resources, so that the implementation of policies in the development of natural tourism in XIII Koto Kampar District has not been implemented properly maximum. Keywords: Policy, Communication, Resources